2018
DOI: 10.1186/s13613-018-0432-4
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygen versus noninvasive ventilation in adult patients with cystic fibrosis: a randomized crossover physiological study

Abstract: BackgroundNoninvasive ventilation (NIV) is the first-line treatment of adult patients with exacerbations of cystic fibrosis (CF). High-flow nasal oxygen therapy (HFNT) might benefit patients with hypoxemia and can reduce physiological dead space. We hypothesized that HFNT and NIV would similarly reduce work of breathing and improving breathing pattern in CF patients. Our objective was to compare the effects of HFNT versus NIV in terms of work of breathing, assessed noninvasively by the thickening fraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
3
34
1
Order By: Relevance
“…36 No effects were observed on transcutaneous CO 2 in this physiologic study, which included 15 subjects ventilated with HFNC and NIV for 30 min in a cross-over random order, which was probably due to the short duration of HFNC treatment. 37 NIV seemed to have a greater effect on breathing frequency than HFNC in our subjects. We assumed that NIV combined the effect of pressure support and high PEEP to improve breathing frequency more quickly than HFNC, for which PEEP is limited, especially when suboptimal nasal flow was administered (ie, < 60 L/min) or when the mouth of the patient was open.…”
Section: Discussioncontrasting
confidence: 43%
“…36 No effects were observed on transcutaneous CO 2 in this physiologic study, which included 15 subjects ventilated with HFNC and NIV for 30 min in a cross-over random order, which was probably due to the short duration of HFNC treatment. 37 NIV seemed to have a greater effect on breathing frequency than HFNC in our subjects. We assumed that NIV combined the effect of pressure support and high PEEP to improve breathing frequency more quickly than HFNC, for which PEEP is limited, especially when suboptimal nasal flow was administered (ie, < 60 L/min) or when the mouth of the patient was open.…”
Section: Discussioncontrasting
confidence: 43%
“…For Study B, Friedman test and Dunn multiple comparisons were used to compare the different values of parasternal intercostal muscle thickening and diaphragm thickening fraction across conditions. Sample size was estimated from previous publications 17,20 and a convenience sample of 16 patients was deemed necessary.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In stabilized patients with Cystic Fibrosis, no differences in work of breathing as measured by diaphragmatic activity were observed while patients were at baseline, on HFNT or on NIV. However, HFNT resulted in mild improvement in VT compared to NIV and reduced RR compared to COT [94].…”
Section: Positive Airway Pressurementioning
confidence: 88%
“…Interestingly long-term studies have shown that HFNT is well tolerated, and reduces dyspnea compared to LTOT [41, 42], but when used in the short-term HFNT does not provide similar results in patients with COPD or CF [90,91,94]. Despite the lack of side effects, patients have reported overall comfort to be better or similar on LTOT and NIV compared to HFNT the delivered flow was 30 L/min [101].…”
Section: Effects On Comfortmentioning
confidence: 99%